Kajian Faktor yang mempengaruhi Wanita dalam Membangun Usaha Bidang Perhotelan dan Restoran (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2016)
This study aims to determine the factors that affect women in their role as an entrepreneur in the field of hotel and restaurant, how they overcome the factors that caused the barrier to their business, and how they apply positive factors in their strategy to run their business. Respondents in this study were 50 business women (entrepreneur) in the field of the accommodation and food, located in Jakarta and Bandung. The method used was descriptive method to describe or depict phenomena or relations among the phenomena studied systematically, factual and accurately. The variable in this study was the factors that affect women in developing their business, especially in the accommodation and food business. Subvariables in this study were four factors, i.e. family, education, capital and social. The results showed that the biggest deterrent factor is the capital, but they have their own strategies to overcome this factor. For other factors, namely family, education and social, the respondents revealed their positive factor towards business and capable of implementing the business strategy accordingly.